Dynamic Properties and Fatigue Life of Stone Mastic Asphalt Mixtures Reinforced with Waste Tyre Rubber. (24th October 2013) - Mashaan, Nuha Salim; Ali, Asim H.; Koting, Suhana; Karim, Mohamed Rehan
Abstract : Today, virgin polymer modified asphalt mixes are comparatively more expensive for road pavement. One way to reduce the expense of such construction and to make it more convenient is the application of inexpensive polymer, such as waste polymer. The primary aim of this study was to investigate the effect of adding waste tyre rubber (crumb rubber modifier (CRM)) on the stiffness and fatigue properties of stone mastic asphalt (SMA) mixtures. Various percentages of waste CRM with size of 0.60 mm were added to SMA mixtures. Indirect tensile stiffness modulus test was conducted at temperatures of 5, 25, and 40°C. Indirect tensile fatigue test was conducted at three different stress levels (2000, 2500, and 3000 N). The results show that the stiffness modulus of reinforced SMA samples containing various contents of CRM is significantly high in comparison with that of nonreinforced samples, and the stiffness modulus of reinforced samples is in fact less severely affected by the increased temperature compared to the nonreinforced samples. Further, the results show that CRM reinforced SMA mixtures exhibit significantly higher fatigue lives compared to the nonreinforced mixtures help in and promotion of sustainable technology by recycling of waste materials in much economical and environmental-friendly manner.